Miasto tańca — transformacja przestrzeni post-industrialnej w centrum kultury na przykładzie Bytomia i Śląskiego Teatru Tańca - Mikrut-Majeranek, Magdalena (Studia Etnologiczne i Antropologiczne, 2013)
A change concerning a paradigm of perceiving an industrial local space has taken place for the period of the last twenty years. The very phenomenon happens not only in Poland , but also all over Europe, the example of which might be such places as the Slovenian Stara Elektrarna, Estonian Kanuti Gildi SaaL centre, Warsaw Stara Papiernia centre, Wałbrzych “Julia” or Bytom “Rozbark” Coal Mines. The artistic movement developing there takes over postindustrial objects transforming them into cultural centres. Thanks to revitalization, the restoration of towns aiming at transforming the buildings that are no longer used into dynamically developing cultural institutions. The aim of the article is to bring the changes of former “Rozbark” Coal Mine and Silesian Dance Theatre in Bytom closer.